Analysis of Flood Vulnerability Levels Using Overlay Method with System-Based Scoring Geographical Information (Case Study: District Tangerang) - Itah Safitri; Yayat Ruhiat; asep saefullah (UNIB Press, 2023)
This research aims to determine the factors of flood disasters in Tangerang district, which consist of land height, slope, soil type, land use, river density, and rainfall, and to find out the results of flood mapping in Tangerang district. The research method used is the overlay method with scoring. This research uses secondary data consisting of rainfall data for the period 2022-2020, shp Admin data from Tangerang district, watershed data throughout Indonesia, OSM data throughout Indonesia, slope data throughout Indonesia, DEM data throughout Indonesia, DSMW data throughout Indonesia, 2017 landcover data. Data were processed using Microsoft Excel software, Arc GIS 10.8, and QGIS 3.26.0. Based on the results obtained, the flood disaster factors in Tangerang district that are very dominant in influencing the occurrence of floods in Tangerang district are soil type and slope. Meanwhile, the results of flood mapping in Tangerang district are categorized into three classes: not vulnerable, moderately vulnerable, and fragile. Four sub-districts in Tangerang Regency are not prone to flood disasters, including Panongan, Legok, Cisauk, and Pagedangan sub-districts. Meanwhile, the Tangerang district, which is categorized as quite vulnerable, consists of 9 sub-districts, namely the sub-districts of Kelapa Dua, Curug, Cikupa, Tigaraksa, Jambe, Solear, Jayanti, Cisoka, Balaraja. Meanwhile, there are 16 sub-districts in Tangerang Regency which are categorized as very vulnerable, namely Pasar Kemis, Sindang Jaya, Kresek, Gunung Kaler, Sukamulya, Sepatan, Sepatan Timur, Rajeg, Kemiri, Kronjo, Mekar Baru, Mauk, Sukadiri, Pakuhaji, Teluk Naga, Kosambi districts.